Muslim Mughal Women’s Contributions: Building a Legacy of Learning and Giving - Sarwar, Halima; Pervaiz, Dr. Huma (Al-Irfan, 2024)
This article examines the significant contributions of Mughal royal women to the empire’s social fabric, focusing on their roles in philanthropy, education, and cultural activities. Contrary to the traditional historiography, which frequently confines the roles of elite Muslim and non-Muslim women to political influence alone, this research, employing the Structuration theory, expands the perspective on their agency in medieval India by showcasing their active involvement in social, religious, and educational domains. This study also investigates their philanthropic activities—comprising the erection of madrassas and mosques, helping the needy—had a notable impact on reinforcing the religious strength of the Muslim subjects. Additionally, the study investigates how extravagant feasts and fairs, including Nauroz and Meena Bazaar, offered these women opportunities to showcase their wealth, engage in economic activities, and build social acquaintances within the nobility. Drawing on various historical sources this research illuminates how these women utilized both the assets and restrictions of the harem to nurture the societal progress. Through this nuanced examination, the article emphasizes the interplay of gender, power, and philanthropy, revealing the pivotal role of Muslim royal women in shaping the sociopolitical and cultural legacy of Mughal Empire.